The Christian God: Collected Essays - C. Ullrich (Acta Theologica)
The book "The Christian God: Collected Essays" by Shutte, A. (Ed. Patrick Giddy), (Johannesburg: UJ University Press, 2024), ISBN 1923206370 is reviewed.